Work Fatigue in Transport Workers at Bulog Warehouse, Sub-Divre of Masssar City - Pamungkas, Raden Mas Bayu; Russeng, Syamsiar; Kalla, Ruslan (Journal of Aafiyah Health Research (JAHR), 2022)
Background: Fatigue is one of the problems that are often experienced by workers, so that this condition affects their health and in turn will reduce work efficiency and productivity. Aim: The purpose of this study was to determine the factors that affect work fatigue on transport workers in the Bulog Warehouse, Makassar City Sub Division. Method: The research design used was analytic observational with a cross sectional study approach. The total population is 58 resource persons. The sampling technique used the probability sampling method by means of exhaustive sampling, namely taking all members of the population as a sample, namely the entire workforce of 58 people. Data analysis carried out was univariate and bivariate as well as multivariate with chi square test with a significant level (α) = 0.05. Results: The study showed that the variables related to work fatigue on transport workers at the Bulog Warehouse, Makassar City Division, namely the age of the informant (p = 0.000) < 0.05, working period (p = 0.000) < 0.05 and workload (p = 0.000 ) < 0.05, while the individual variables that did not have a significant relationship with work fatigue were gender and nutritional status, for the overall work environment variables there was no relationship to work fatigue of transport workers, namely noise, lighting and room temperature. The variables that have the greatest correlation with work fatigue of the transport workers in the Bulog Divre Warehouse in Makassar City are age (p=0.017) and years of service (p=0.004). Conclusion:There is a relationship between age, period of work and workload with work fatigue on transport workers at the Bulog Warehouse, Sub-Divre Makassar. Also, the age variable or the age of the workforce is the variable that is most closely related to work fatigue on the Transport Workers in the Bulog Warehouse, Makassar Sub-Divisional Division.